Kemampuan Berbahasa Jawa Krama Inggil Peserta Didik Madrasah Ibtidaiyah - Utami, Faricha Ajeng Mega; Rosyidi, Zudan (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
The Javanese Krama Inggil language is currently rarely used. Students at Madrasah Ibtidaiyah prefer neutral Javanese and ngoko innocent rather than Javanese Krama Inggil. The reason they prefer ngoko plain is because it is easier to pronounce and easier to understand. This research aims to describe the Javanese language skills of Krama English students at Madrasah Ibtidaiyah. This research was designed using a qualitative phenomenological approach. The object studied was students' ability to speak Javanese Krama Inggil and the subjects of this research were students at one of the private Madrasah Ibtidaiyah in Lamongan. This research uses qualitative methods to collect observation, interview, and documentation data. The data analysis technique used is phenomenology data analysis, which prioritizes data analysis through experienced phenomena. The research results show that some students still have minimal Javanese language skills and are not yet in accordance with the rules. However, students' Javanese language skills will increase substantially as time goes by. Learners often feel imperfections in their understanding of the language, and they believe that some aspects of the language can be changed to make it more interesting and easier to pronounce.